2019
DOI: 10.1002/prp2.496
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic variability of beta‐adrenergic blocking agents used in cardiology

Abstract: The aim of this study was to evaluate the pharmacokinetic variability of beta‐adrenergic blocking agents used in cardiology by reviewing single‐dose and steady‐state pharmacokinetic studies from the literature. PubMed was searched for pharmacokinetic studies of beta‐adrenergic blocking agents, both single‐dose and steady‐state studies. The studies included reported maximum plasma concentration (C max ) and/or area under the concentration curve (AUC). The coefficient of variation (CV%) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
4
19
0
6
Order By: Relevance
“…However, for LQT2, propranolol might be a relatively better choice. The different efficacies of BBs was primarily due to the pharmacological and pharmacokinetic characteristics of each blocker ( Ågesen et al, 2019 ) ( Figure 6 ). Generally, long-term safety and effectiveness have to be considered for BB treatments in the clinical management of LQTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, for LQT2, propranolol might be a relatively better choice. The different efficacies of BBs was primarily due to the pharmacological and pharmacokinetic characteristics of each blocker ( Ågesen et al, 2019 ) ( Figure 6 ). Generally, long-term safety and effectiveness have to be considered for BB treatments in the clinical management of LQTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a further analysis according to the type of beta-blocker used was only performed in the study by McCourt et al, which showed no impact on MSS [26]. A recent review study conducted by Ågesen et al [27] tried to define the individual bioavailability of beta-blockers used in cardiology. A significant variation has been shown and this may be a confounding factor when trying to investigate the effect of the drugs in cancer patients, since dose adjustments and the timing of the treatment could be crucial when evaluating a possible favorable effect.…”
Section: Discussionmentioning
confidence: 99%
“…We included all Medi‐Cal beneficiaries older than 18 years of age who were continuously enrolled in the FFS program for a minimum of 12 months and were initiated on a β‐blocker undergoing CYP2D6 metabolism as a primary route of elimination (metoprolol, propranolol, labetalol, carvedilol, or nebivolol) between January 1, 2004, and December 31, 2011 20–25 . For those patients who were also prescribed an antidepressant subsequent to the β‐blocker prescription, we required continuous enrollment in the FFS program for at least 12 months before the initial prescription for the antidepressant medication and 2 months immediately after the initial antidepressant prescription.…”
Section: Methodsmentioning
confidence: 99%